Worker separation under performance pay: Empirical evidence from Finland - Derek C. Jones; Panu Kalmi; Takao Kato; Mikko Mäkinen (Bank of Finland, 2017)
This paper investigates the role of individual incentive (II) and group incentive (GI) pay as determinants of worker separation. We use a large linked employer-employee panel data set for full-time male manufacturing workers during 1997-2006 from Finland. We follow actual job spells and switches of individual employees and define separation as worker exit from his current employer. The key finding for white-collar workers is that group incentive pay is associated significantly with increased probability of separation and hence diminished employment stability, but in large firms only. For blue-collar workers our results consistently indicate that individual incentive pay is associated with a decreased probability of separation and hence enhanced employment stability, both in small and large firms. Our finding that group incentive pay increases the risk of separation for white-collar workers is more consistent with theoretical work such as Lazear (2000) and Fehr and Gaechter (2000), while uncovering that individual incentive pay decreases employment stability for blue-collar workers supports theoretical work such as Parent (1999) and Paarsch and Shearer (2000).
URN:NBN:fi:bof-201710171634
Keywords: J33; M52; J31; J62; J63; 330